Development of a Guidebook for Green Skills Implementation in Vocational Schools to Support Green Economy Transformation - Suhendra, Tatang; Subagiyo, Lambang; Basir, Abd (research, training and philanthropy institution Natural Aceh, 2025)
The transformation towards a green economy has become one of the global priorities in addressing climate change and environmental degradation. This research aims to develop a guidebook for implementing green skills in Vocational High Schools (SMK) to support the transformation to a green economy. Green Skills are the knowledge, abilities, values, and attitudes needed to live, develop, and support sustainable and resource-efficient communities. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at SMK Kehutanan Negeri Samarinda, with subjects consisting of 102 tenth-grade students. The guidebook's validity, practicality, and effectiveness were tested through questionnaires and observations. The research results show that the developed guidebook meets the criteria of validity (83%), practicality (82.5%), and effectiveness (81%). This guidebook can enhance students' understanding, skills, and attitudes toward applying sustainability concepts in the context of a green economy.